Durability evaluation of three generations of 100% repeatedly recycled coarse aggregate concrete. (20th June 2019) - Zhu, Pinghua; Hao, Yali; Liu, Hui; Wei, Da; Liu, Shaofeng; Gu, Lei
Highlights: Utilization of RCA for structural concrete after three generations is feasible. The properties of RA gradually deteriorate as the recycling cycles increase. The durability of RAC tends to deteriorate with increasing of recycling cycles. Three generations of RAC can be used as structural concrete for at least 50 years. Abstract: Recycling of construction and demolition wastes (C&DWs) can not only address environmental pollution problems but can also produce abundant profits. Using repeatedly recycled coarse aggregate (RCA) to prepare structural concrete is an important means for addressing the economic, environmental, and social problems caused by the shortage of natural aggregate resources. In this study, the durability of three generations of 100% repeatedly recycled aggregate concrete (RAC) was investigated to evaluate the effect of using RCA from various recycling cycles. The first-generation RCA was purchased, while the second and third generations of RCA were prepared in the laboratory, based on the principle of equal carbonization depth. All the aggregates were crushed and sieved to eliminate the difference in size distribution between the RAC mixes in each cycle. The results show that the qualities of the RCA that affect the durability of concrete deteriorate with increasing number of recycling cycles. Durability metrics of the RAC (freeze-thaw resistance, chloride ion permeability coefficient, and carbonization depth) decrease gradually with increasing number of recycling cycles. However, the RCA in each cycle could meet the requirements for structural concrete aggregates, and concrete utilizing RCA can be designed as structural concrete with a life span of at least 50 y.